SISTEM INFORMASI PENGENALAN DESTINASI WISATA DAN KULINER PROVINSI JAWA TENGAH BERBASIS ANDROID - Reza Pratama (CV. Multi Kreasi Media, 2024)
Each region in Indonesia has its own characteristics, starting from the culture of the people, culinary and historical places, for example, Central Java Province. However, many tourists have a little difficulty finding references regarding recommendations for the right tourist and culinary destinations when visiting this province. There needs to be a media that can provide information, so that it is hoped that it will make it easier for tourists to access tourist and culinary information in the province of Central Java, for example by designing an application on a smartphone device. The application that will be built with IONIC and MySQL as the database, and the method for storing the data itself uses the Rational Unified Process (RUP) method.